Analisis Kualitas Website BPJS (Badan Penyelenggara Jaminan Sosial) Kesehatan Menggunakan Metode Webqual 4.0 - Nur Afifa, Ifa; Sanglise, Marlinda; Julius P.P.Naibaho (The Indonesian Journal of Computer Science, 2024)
As the digital era advances, the use of websites as the main means of providing information and services is increasingly important. One example is the BPJS Health website, which is an important platform for providing health information and services for the Indonesian people. This research aims to evaluate the quality of the BPJS Health website using the WebQual 4.0 method and PLS-based SEM analysis, with a focus on user satisfaction as end users. This research method uses a quantitative approach by collecting data through questionnaires distributed to 118 BPJS Health website users. Analysis was carried out using SmartPLS 4.0 software to test the measurement model (outer loading) and structural model (inner model). The research results show that the Usability and Service Interaction Quality variables have a positive and significant effect on user satisfaction, while Information Quality has a positive but not significant effect.